Developmental Continuity and Change in Physical, Verbal and Relational Aggression and Peer Victimization from Childhood to Adolescence - Ettekal, Idean (Dev Psychol, 2017)
To investigate the developmental course of aggression and peer victimization in childhood and adolescence, distinct subgroups of children were identified based on similarities and differences in their physical, verbal, and relational aggression and victimization. Developmental continuity and change were assessed by examining transitions within and between subgroups from grades 1 to 11. This longitudinal study consisted of 482 children (50% females) and was based on peer report data on multiple forms of aggression and peer victimization. Using person-centered methods including latent profile and latent transition analyses, most of the identified subgroups were distinguishable by their frequencies (i.e., levels) of aggression and victimization, rather than forms (physical, verbal and relational), with the exception of one group that appeared to be more form-specific. Across subgroups, multiple developmental patterns emerged characterized as early- and late-onset, social interactional continuity, desistance and heterotypic pathways. Collectively, these pathways support the perspective that the development of aggression and peer victimization in childhood and adolescence is characterized by heterogeneity.